Photonic molecules modes in resonantly coupled spherical microcavities with semiconductor nanocrystals - Donegan, John; Bradley, Louise (SPIE, 2007)
We present a detailed study of the localized coupled-cavity modes in a photonic molecule formed from two dielectric spherical microcavities with CdTe nanocrystals, which show a multi-peak narrowband modal structure resulting from lifting of the mode degeneracy with respect to the azimuthal quantum number. The feasibility of photonic molecules as the basis for a multi-channel, wavelength-tunable optical delay device is analysed.
Proceedings of SPIE - The International Society for Optical Engineering,
ICONO 2007: Novel Photonics Materials; Optics and Optical Diagnostics of Nanostructures
PUBLISHED
Keywords: Physics